Kombinasi Balance Training dan Core Training Lebih Baik Dari Pada Balance Training Saja dalam Meningkatkan Frekuensi Tendangan Mawashi Geri Atlet Karate Dojo SMAN 2 Praya - Herlina Herlina; Zakir Burhan (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
Karate is a martial art. One of the kick techniques in karate martial arts is mawashi geri. In martial arts, the frequency of this kick is very decisive. This technique, if it hits the right target, will result in 3 points in one kick. This study aims to prove that adding core training to balance training can increase the frequency of mawashi geri kicks in karate athletes. This research is experimental with pre-test and post-test control group design, conducted at the Dojo of SMAN 2 Praya. There were 28 research subjects who were randomly divided into 2 groups, each group consisting of 14 samples. The control group was given only balance training while the treatment group was given a combination of balance training and core training. The control group was given 5 repetitions, 3 sets, 3 times a week for 6 weeks and the treatment group was given 3 repetitions, 3 sets, 3 times a week for 6 weeks for balance training and 2 repetitions, 3 sets, 3 times a week, for 6 weeks for core training. Mawashi geri kick frequency was measured twice pre-post per 10 seconds. Data were analyzed by paired t-test and independent t-test. There was an increase in the frequency of mawashi geri kicks in the > control group from 7.71 ± 0.97 times/10 seconds to 12.35 ± 1.95 times/10 seconds after training (p Treatment group from 7.85 ± 0.96 times/ 10 seconds to 13.71 ± 1.35 times/10 seconds (p (.0.001). The increase in the frequency of the treatment group was 5.85 times/10 seconds higher than (.0.001> the control group 4.57 times/10 seconds (p <0.025). Conclusion: The training of both groups equally affects kick frequency. However, the combination of balance training and core training is better at increasing the frequency of mawashi geri kicks in karate athletes than balance training alone